Schools in a Media-Rich World: Opportunities and Constraints - Szabó, László Tamás (European Journal of Mental Health, 2011)
The present study is an essay-like writing based partly on a – selective – review of the relevant literature and partly on the experiences gained during a multi-year university course. Its thematic foci are the following: mediated environment and learning; information vs. knowledge; the world of media with its values and models; ‘digital folklore’; and ‘homo informaticus’ as a new human race. It gives a description and analysis of the sources and background of new metaphors (such as ‘knowledge-based society’; ‘European Learning Space’ or the ‘European dimensions’ of education) appearing in teaching and learning environments. The study discusses the following questions: is the mediated environment an ‘agora’ for wider social dialogue or a tool for the massive manipulation of the masses? What is the role repertoire of the teacher in the new learning environment? What dynamics are at work in mixed-medium (image and text) communication trends in schools and society; how is the image-text ratio changing and what conclusion can be drawn from this change?